Resveratrol as a potential broad-spectrum compound for cancer treatment - Li Kar Stella Tan; Chee Wun How; Jhi Biau Foo; Kooi Yeong Khaw; Bey Hing Goh; Yong Sze Ong (Progress in Microbes and Molecular Biology)
There is a need to shift the paradigm of cancer therapeutic approach. The severe adverse side effects, drug resistance and unaffordable price plagued with chemotherapeutic drugs has spurred the development of “dirty drug”. Natural products, specifically phytochemicals, have gained much attention due to their ability to target multiple interconnected pathways. Resveratrol (RSV), the stilbenes found in red wine, is one of the phytochemicals that exhibits various pharmacological therapeutic effects including cancer. In this review, we highlighted RSV as a potential “broad-spectrum” anticancer compound, by summarising its targeting mechanisms in the pathways relevant to the cancer hallmarks.